2019
DOI: 10.1002/rcr2.501
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing polychondritis with large airway involvement

Abstract: Relapsing polychondritis is a rare autoimmune condition characterized by episodic and progressive cartilaginous inflammation. Its clinical presentation is vastly divergent and can affect various organs. We report the uncommon case of large airway involvement in a patient presenting with shortness of breath on the background of diagnosed relapsing polychondritis. Computed tomography (CT) chest demonstrated thickening of the cartilaginous portions of the trachea and bronchi with sparing of the posterior membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Most published cases of RP have presented with auricular inflammation and/or respiratory symptoms, but only a few cases manifested idiopathic orbital inflammation [ 1 , 2 , 16 , 17 , 23 ]. Those cases were commonly associated with ANCA vasculitis, ankylosing spondylitis, systemic lupus erythematosus, or Sjogren’s syndrome; however, none have been reported with reactive arthritis [ 1 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most published cases of RP have presented with auricular inflammation and/or respiratory symptoms, but only a few cases manifested idiopathic orbital inflammation [ 1 , 2 , 16 , 17 , 23 ]. Those cases were commonly associated with ANCA vasculitis, ankylosing spondylitis, systemic lupus erythematosus, or Sjogren’s syndrome; however, none have been reported with reactive arthritis [ 1 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only few reported an association with HIV infection [ 11 14 ]. The mainstay of treatment in most cases was systemic corticosteroids with or without immunosuppressive agents [ 1 , 2 , 16 , 17 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hazra et al reported that respiratory symptoms were associated with the longest delay in diagnosis, with a median delay time of 10.4 years, while leaving 64% of patients pending diagnosis for more than two years [5]. The presence of respiratory symptoms in a patient known to have RP raises the clinical suspicion of airway involvement [15], but it would be challenging to establish the diagnosis of RP in someone presenting only with cough and dyspnoea. Considering the non‐specific and airway‐only manifestation of our patient, it was not helpful to diagnose his RP by applying those aforementioned sets of criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Around 35–40% of patients with known airway involvement eventually required some form of interventions, such as tracheostomy, balloon dilatation, stenting, or a combination [2,3,10]. Moreover, for patients with long‐standing RP, life‐threatening airway collapse could be the first manifestation to unveil occult airway involvement [15]. The treatment of RP is largely based on experiences from previous case reports and small series, and there are still no evidence‐based guidelines [1,3,17].…”
Section: Discussionmentioning
confidence: 99%
“…The diverse and nonspecific clinical features of RP alongside its relative rarity frequently lead to a diagnostic delay [ 8 ] which is associated with the lack of ear, nose, or joint involvement but presents with early signs of intermittent arthritis or eye involvement in such cases [ 4 ]. RP patients may develop significant disabilities during the course of the disease such as hearing and visual impairments, and 30–50% of patients suffer pulmonary complications [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%